Ibericancridae, a new dakoticancroid family (Decapoda, Brachyura, Podotremata) from the upper Campanian (Upper Cretaceous) of Spain - Artal, Pedro; Guinot, Danièle; van Bakel, Barry; Castillo, Juan (Zootaxa, 2008)
A small faunule of crabs from the upper Campanian (Upper Cretaceous) of Valencia, eastern Spain, is described as Ibericancer sanchoi n. gen., n. sp., and assigned to a new family, the Ibericancridae n. fam., which is placed in the Dakoticancroidea Rathbun, 1917, until now known to comprise a single family, Dakoticancridae Rathbun, 1917, restricted to the Upper Cretaceous of North America and northeast Mexico. The Ibericancridae n. fam. shares with the Dakoticancridae the general shape and size of the carapace, the arrangement of dorsal regions of the carapace, a pleural suture situated at carapace flanks, insertion of a sternal thoracic portion between abdomen and coxae of the pereiopods, and long P2 and P3. Ibericancer n. gen. differs from the four genera currently included in the Dakoticancridae (Dakoticancer Rathbun, 1917; Tetracarcinus Weller, 1905; Avitelmessus Rathbun, 1923 and Seorsus Bishop, 1988), in having P4 and P5 conspicuously reduced and subdorsal in position, a narrower thoracic sternum, and distinct frontal and orbital features. Because the male and female gonopores are located on the pereiopods, P5 and P3 coxae, respectively, and the spermathecal aperture is at the extremity of the thoracic suture 7/8, the Dakoticancroidea conforms to the Podotremata Guinot, 1977. It is here interpreted as a carcinised podotreme superfamily, the broadening of the thoracic sternum being weak in the Ibericancridae n. fam., but distinct in the Dakoticancridae. Dakoticancroid crabs probably employed a carrying behaviour, as do most podotremes, and were characterised by an abdominal holding of the press button type. Morphological characters of the Ibericancridae n. fam. add significantly to our knowledge of the evolutionary processes within the Podotremata.